Majaz dalam Kitab Asror Balaghoh Perspektif Abdul Qohir Al Jurjani (Analisis Majaz dalam Maulid Simthud Duror) - Puziyana Widya Ningrat; Ahmad Dardiri; Raswan Raswan; Achmad Fudhaili (Universitas Muhammadiyah Mataram, 2026)
The study of majaz in the classical balaghah tradition plays an important role in understanding the beauty and depth of meaning in Arabic literary texts, especially religious works. However, the analysis of majaz in Maulid Simṭud Durar based on the perspective of ʿAbd al-Qāhir al-Jurjānī is still limited. This study aims to analyse majaz in Maulid Simṭud Durar based on the concepts in Asrār al-Balāghah in order to provide theoretical and practical contributions. The research uses a qualitative method with a Systematic Literature Review (SLR) approach and a literature study of 15 relevant scientific literatures. The instruments are document analysis sheets and data classification tables, with reduction, categorisation, and descriptive-analytical conclusion drawing techniques. The results of the study indicate that majaz and tasybih in Maulid Simṭud Durar function as semantic and aesthetic devices that strengthen the spiritual dimension of the text and are relevant as examples for learning the science of Bayan. Implicitly, this study enriches the development of balaghah and the study of Arabic religious literature.